2014
DOI: 10.1186/1472-6882-14-175
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of Euterpe oleracea Mart. in malignant cell lines

Abstract: BackgroundEuterpe oleracea Mart., a plant from the Amazon region, is commonly known as açaí or juçara; it has high nutritional value and elevated levels of lipids, proteins, and minerals. Açaí is an abundant and much consumed fruit by the Amazon local population, and studies have demonstrated that it is rich in phytochemicals with antioxidant, anti-inflammatory, and anticancer activities. Therefore, the aim of this study was to test this plant for anticancer activity in different human malignant cell lines.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 30 publications
5
42
0
2
Order By: Relevance
“…To our knowledge, this report is the first study to evaluate the anti-inflammatory and antiangiogenic effects of açaí in endometriotic implants. Notably, our study used the hydro-alcoholic extracted from açaí stones because this extract was previously described to be more active than the pulp extract [25,37]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this report is the first study to evaluate the anti-inflammatory and antiangiogenic effects of açaí in endometriotic implants. Notably, our study used the hydro-alcoholic extracted from açaí stones because this extract was previously described to be more active than the pulp extract [25,37]. …”
Section: Discussionmentioning
confidence: 99%
“…Silva et al . demonstrated the anticancer activity of açaí in different malignant cell lines [25]. These authors concluded that the extract exhibited anti-tumorigenic potential in the human breast cancer MCF-7 cells and reduced viability and morphological alterations [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this extract did not show toxicity to non-tumor cells (primary cultures of liver cells, PLP2). To our knowledge, Silva et al (2014), was the only report found in literature that performed cytotoxic effects using cell lines derived from breast and colorectal adenocarcinomas (Caco-2, HT-29, MDA-MB-468 and MCF-7) with different parts of açaí, including its seeds. These authors concluded that an ethanol/water seed extract was significantly more effective against the MCF-7 cell line than total fruit and bark extracts.…”
Section: Bioactive Propertiesmentioning
confidence: 99%
“…Silva et al (2014) conducted a study with the açaí fruit including the seeds, evaluating the cytotoxic effects in malignant cell lines and concluded that the seeds present a higher polyphenols content compared to the pulp being its antimutagenic potential was also higher. The same authors have warned of the need for further studies to characterize the compounds responsible for these effects.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of EOO tested were 0.1, 0.5, 1, 2.5, 5, 10, 25, 50, 100, 250, 500, 800, and 1000 μg/mL, and the results after 4-and 24-h exposure to EOO showed that none of the tested concentrations induced cytotoxic effects in both cell types analyzed (cell viability was above 80%). On the other hand, Silva et al (2014) observed that bark, seed, and total açaí fruit hydroalcoholic extracts showed cytotoxicity (and antitumorigenic potential) in the human breast cancer cell line (MCF-7), but not in colorectal adenocarcinoma cells, also by using the MTT assay. The differences in the extract composition, protocols, and cell types analyzed could explain the differences in the cytotoxic effects observed in these two studies between themselves and our present study.…”
Section: Resultsmentioning
confidence: 99%